Governing the World. Issue 142 (November 2015) - Oliver, Caroline
Abstract : Board Leadership Editor Caroline Oliver interviews Otto Spijkers, Assistant Professor of Public International Law at Utrecht University and researcher at the Utrecht Centre for Water, Oceans and Sustainability Law.